Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.14598
|View full text |Cite|
|
Sign up to set email alerts
|

Matrine alleviates lipopolysaccharide-induced intestinal inflammation and oxidative stress via CCR7 signal

Abstract: The aim of this study was to investigate the protective effects of matrine on lipopolysaccharide (LPS)-induced inflammation and oxidative stress in vivo and in vitro. The results showed that matrine improved intestinal inflammatory status and oxidative balance and enhanced chemokine receptor 7 (CCR7) expression. In LPS-challenged mice and Caco-2 cells, matrine alleviated LPS-induced inflammation and oxidative stress via downregulating pro-inflammatory cytokines (IL-1β and IL-17) and malondialdehyde (MDA) produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Thus, resolution of inflammation is key to treat COPD. In the present study, we tested the hypothesis that matrine could suppress inflammation in the airway of mice exposed to CS based on its anti-inflammatory effect in other inflammatory diseases [29,37]. In our in vivo and ex vivo studies, we found that matrine dampened airway inflammation by reducing the influx of neutrophils but not macrophages in the airways of CS-exposed mice.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, resolution of inflammation is key to treat COPD. In the present study, we tested the hypothesis that matrine could suppress inflammation in the airway of mice exposed to CS based on its anti-inflammatory effect in other inflammatory diseases [29,37]. In our in vivo and ex vivo studies, we found that matrine dampened airway inflammation by reducing the influx of neutrophils but not macrophages in the airways of CS-exposed mice.…”
Section: Discussionmentioning
confidence: 83%
“…Matrine and its different derivatives were reported to have multiple effects in different disease models. For example, matrine can prevent bone loss [38], protect glial cells from central nervous system inflammation [39], alleviate intestinal inflammation [29], and decrease liver cell injury [40]. Additionally, it is reported that matrine showed very strong anti-tumor effect which includes cytotoxic effect on prostate tumor cells, bladder tumor cells, and breast cancer cells [31,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the biological activities of matrine are more relevant to other applications of Ku-Shen other than anti-tumor activities. It is reported to possess a variety of pharmacological activities, including antipyretic ( Cho et al, 1986 ; Xiang and Jiang, 2013 ), antiepileptic ( Xiang and Jiang, 2013 ), antinociceptive ( Wang et al, 2013 ; Dun et al, 2014 ), anti-inflammatory ( Zhang B. et al, 2011 ; Wu G. et al, 2017 ), myocardial preservation ( Zhang et al, 2006 ), antifibrotic ( Zhang et al, 2001 ), anti-tumor ( Wu J. et al, 2017 ), anti-viral ( Li et al, 2005 ) and anti-angiogenic ( Li et al, 2010 ). Our predicted results demonstrated that matrine could target a molecular network related to multiple functions, which is consistent with the multi-target nature of traditional medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a proven group of Chinese patent medicines has held and still holds an important position in the treatment of a variety of cancers in China, and statistical analysis results from nationwide medical insurance data have suggested that Sophorae Flavescentis Radix , namely Ku-Shen , is widely used in the treatment of a variety of cancers in China ( Wu et al, 2015 ). Matrine is a main active constituent in Ku-Shen which has been approved as herbal medicine in China, and has polypharmacology including anti-inflammatory ( Zhang B. et al, 2011 ; Wu G. et al, 2017 ), anti-tumor ( Wu J. et al, 2017 ), anti-angiogenic ( Li et al, 2010 ) and so on. It is a kind of quinolizidine alkaloid compound and very similar in structure to oxymatrine and sophoridine.…”
Section: Introductionmentioning
confidence: 99%